Household Attitudes towards Sustainable Management of Urban Green Spaces and Parks in Lagos State, Nigeria - Ajewole, O. C.; Adebo, G. M.; Fadipe, B. O. (Advances in Social Sciences Research Journal, 2019)
The attitude of urban dwellers is essential to the sustainable management of green spaces and parks in their environment. The study was carried out to examine various ways of raising fund, preferred mode of contribution and determinants of mode of contribution of the respondents to sustainable management of urban green spaces and parks. A total of 120 respondents were purposively selected based on the existence of green spaces and parks in six local government areas of Lagos state, Nigeria, Frequency counts, percentages and multivariate Probit regression model were used to analyze the data. The result shows that voluntary donations and Tax were rated by 40.8% of the respondents respectively as the most viable way of generating funds for sustainable management and maintenance of urban green spaces and park in Lagos state. Also, 46.67% of the respondents were willing to donate or pay cash as their means of contributing to sustainable management of green spaces and parks, while 6.67% were not willing to donate or render any assistance for sustainable management of green spaces and parks. The study affirmed that the Sex, Marital status, and average monthly income of the respondents had positive and significant influence on the respondents’ contribution to sustainable management of urban green space and parks, while educational level had a negative influence on the mode respondents’ contribution to sustainable management of green spaces and parks.